ART INTERVENTION IN THE SUB-URBAN AREA VISUAL CHARACTERISTIC - . Adityo (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2019)
Indonesia Art Institute of Yogyakarta is one of well- known art college in Indonesia. This institution has graduated many Indonesian famous artists. Located at Sewon, Bantul, this institution has a significant effect on the suburban area development of the institution surrounding area. The art atmosphere of surrounding area shaped by Art-activities that happened there. Many formal or informal artspace also located there stimulate the activities to become intense and sustain. Beside that One thing that enriching the art atmosphere is mural drawing that done in private properties in the public spaces. The mural drawing spreading around the suburban area surrounding the college building. 20 mural has been recorded only in one village, and its enrich the visual aspect of the sub-urban area and beautifully blending to the suburban area. The mural draws also expresses a message for people who have seen it as a sightseeing object and makes the suburban area as a public artwork gallery. This research aims to know the factors how the mural drawing can be blend to the area and strengthen the place identity of the area by knowing the relationship between mural drawing and where it is made. Observation has been done in the sub-urban area surrounding the Indonesia art institute of Yogyakarta. The concept of the mural is contextual to the site. Its usually represent the social or environmental issue that happens there. The space and sensitivity of selection the mural drawing theme not only make the artwork blended naturally with the area but improve place-identity of the area. Furthermore the phenomena have potential to be a theme of this suburban area development.